Germline mutations of 4567 patients with hereditary breast-ovarian cancer spectrum in Thailand - Chalermkiat Kansuttiviwat; Pongtawat Lertwilaiwittaya; Ekkapong Roothumnong; Panee Nakthong; Peerawat Dungort; Chutima Meesamarnpong; Warisara Tansa-Nga; Khontawan Pongsuktavorn; Supakit Wiboonthanasarn; Warunya Tititumjariya; Nannipa Phuphuripan; Chittapat Lertbussarakam; et al. (npj Genomic Medicine, 2024)
Abstract Multi-gene panel testing has led to the detection of pathogenic/likely pathogenic (P/LP) variants in many cancer susceptibility genes in patients with breast-ovarian cancer spectrum. However, the clinical and genomic data of Asian populations, including Thai cancer patients, was underrepresented, and the clinical significance of multi-gene panel testing in Thailand remains undetermined. In this study, we collected the clinical and genetic data from 4567 Thai patients with cancer in the hereditary breast-ovarian cancer (HBOC) spectrum who underwent multi-gene panel testing. Six hundred and ten individuals (13.4%) had germline P/LP variants. Detection rates of germline P/LP variants in breast, ovarian, pancreatic, and prostate cancer were 11.8%, 19.8%, 14.0%, and 7.1%, respectively. Non-BRCA gene mutations accounted for 35% of patients with germline P/LP variants. ATM was the most common non-BRCA gene mutation. Four hundred and thirty-two breast cancer patients with germline P/LP variants (80.4%) met the current NCCN genetic testing criteria. The most common indication was early-onset breast cancer. Ten patients harbored double pathogenic variants in this cohort. Our result showed that a significant proportion of non-BRCA P/LP variants were identified in patients with HBOC-related cancers. These findings support the benefit of multi-gene panel testing for inherited cancer susceptibility among Thai HBOC patients. Some modifications of the testing policy may be appropriate for implementation in diverse populations.